The Extent to Which Lecturers at Jordanian Universities Utilize Infographic Guidelines for Curriculum Design - Fraihat, Nesreen Bassam; Alenezi, Raheeq Soudan; Alenezi, Areej Soudan; Alkhalaileh, Mohannad S. (International Journal of Membrane Science and Technology, 2023)
This research aims to discover the degree to which faculty members use educational infographic design standards in computerized courses. So, the study adopted the descriptive analytical method; a questionnaire was used to collect data and then distributed to a sample of 149 faculty members in Jordanian universities. Accordingly, the study results showed that the degree of use of educational infographic design standards by faculty members in Jordanian universities in computerized curricula is moderately high. In addition, there indicated no statistically significant differences in the estimates of faculty members in Jordanian universities due to gender and the certificate source.